Situation Report: Bulgaria, 24 September 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. 40th Anniversary Celebrated / by Rada Nikolaev Recent Trends in the Bulgarian Military / by Rada Nikolaev Arable Land Hard Hit by Erosion / by Pravda Dimtcheva Summer Student Brigades in Agriculture: A Rotten Tomato? / by Deana Tosheff